Wars, depression, and Fascism: Income inequality in Italy, 1900-1950 - Maria Gómez León; Giacomo Gabbuti (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
This paper shows yearly estimates of income inequality in Italy from 1900 to 1950. By constructing dynamic social tables, we comprehensively assess inequality across all components of Italian society. In a context of declining inequality across Europe, interwar Italy reveals a singular trajectory with a rise in inequality during WW1, markedly reversed during 1918-1922, resumed after the March on Rome and with a further increase during WW2. While consolidating the reinterpretation of inequality in interwar Europe, by showing so far overlooked short-term distributive shocks in Italy, our findings confirm the regressive nature of Italian Fascism.
Keywords: D31; E24; E25; J31; N34; 330; Fascist Italy; income inequality; interwar Europe; dynamic social tables